Elucidating and Utilising the Mechanisms Used by Pseudomonas aeruginosa to Develop Resistance to Bacteriophages to Aid Therapeutic Formulation and Application in Cystic Fibrosis - Vaitekenas, Andrew (Curtin University, 2023)
Antimicrobial resistance (AMR) is one of the greatest threats to human healthcare and this thesis explored the use of bacteriophages to treat Pseudomonas aeruginosa infections. Firstly, responses of clinical isolates of P. aeruginosa to phage treatments were investigated and mechanisms of resistance identified. Potential of phage-antibiotic pairings to prevent the emergence of phage resistance was then explored as well as safety of these combinations using a 3-dimensional cell model of the lung.